DEVELOPING E-BOOK FOR PRE-INTERMEDIATE GRAMMAR IN EFL CLASSROOM - Asep Hardiyanto (UNIVERSITAS MUHAMMADIYAH METRO (MUHAMMADIYAH UNIVERSITY OF METRO), 2020)
The current article attempts to develop teaching material for intermediate grammar in form of electronic book (e-book) which utilize epub format. E-book is assumed to be an interesting learning sources since it utilizes digital media, in which it is suitable with the students’ condition in digital era. This research was carried out by using Research and Development method. In developing e-book, several stages were conducted; pre-liminary research, prototyping phase, and assessment phase. From the assessment result, it was found that three experts in; material, language used and media declared that this e-book is appropriate to be used. Moreover, in term of students’ perception, it was revealed that from aspect relevance (4.0); consistency (3.8); practice (4.4); and effective (4.2) which hence it can be said that students have positive perception toward the use of this e-book.. Therefore, it can be concluded that generally this e-book is very good and recommended to be used in pre-intermediate grammar classroom.